Epidemiological profile of HIV infection in the municipality of Belém, Pará, in the period between 2016 and 2021 (Research, Society and Development, 2022)
Introduction: HIV is the virus responsible for AIDS and it affects all social groups over the Brazilian territory. It can be acquired in many ways, such as unprotected sexual activity. Unfavorable socioeconomic conditions are risk factors for HIV infection. Objective: characterize the HIV epidemiological profile between the years of 2016 and 2021 in the municipality of Belém, Pará. Methodology: Descriptive cross-sectional study with a quantitative approach. The incidence of HIV cases reported in the public database SINAN/DATASUS was analyzed using the following variables: age, gender, education, color and hierarchical exposure category of seropositive individuals (homosexual; bisexual; heterosexual; injectable drug users; vertical transmission; ignored). Results: A total of 1,830 reported cases were found in the 6 surveyed years, and 2018 had the highest HIV incidence rate per 100,000 habitants (34,45). In the distribution by variables, the cases predominance was for men, with incomplete elementary school or complete high school, brown, aged between 20 to 49 years and heterosexuals, followed by the homosexuals. Conclusion: The city’s HIV epidemiological profile was characterized in a way that highlighted the most affected social groups, the impact of Covid-19 in Belém’s HIV testing system and the large amount of ignored or blank data in SINAN/DATASUS database (which led to a limited profile observation).